PREVALENSI ANEMIA DAN KEK PADA IBU HAMIL DI PUSKESMAS BAWANG 1 BANJARNEGARA - Aldiansyah, Aldiansyah; Utami, Tin; Surtiningsih, Surtiningsih (NHM PRESS, 2024)
Anemia and CED are more common in pregnant women because of significant changes in their bodies. In this study, all pregnant women at the Bawang 1 Banjarnegara Community Health Center will have their prevalence of anemia and Chronic Energy Deficiency (KEK) assessed. We shall employ a quantitative descriptive research design. The sampling strategy employed in this study is complete sampling, which uses the 80 respondents the entire population as a sample. Secondary data was gathered for this study using KIA books, medical records, and chronological books. This study employed uvariate analysis, which included the mother's anemia, CED status, birth age, and pregnancy status. The study's findings demonstrate that the pregnant women at the Bawang 1 Banjarnegara Community Health Center are known to be between the ages of 20 and 35, with the majority of their parities falling into the Multigravida group. At the Bawang 1 Banjarnegara Community Health Center, the majority of expectant mothers do not have anemia or CED. Anemic pregnant women with Primigravida parity typically fall within the 20–35 age range. Conversely, primigravida parity pregnant women with CED fall within the age range of 20 to 35.